Efficiency Of The Drug Free Village (Village Program Shines In The City Of Semarang - Febriana, Anita; Yuniningsih, Tri; Putranti, Ika Riswanti (Jurnal Ners, 2024)
The Drug-Free Village program, known as "Desa Bersinar" in the City of Semarang, aims to combat drug abuse and promote a healthy, safe environment. This study evaluates the efficiency of the program's implementation by examining its planning, execution, and outcomes in reducing drug-related activities. Utilizing a mixed-method approach, data was collected from both quantitative surveys and qualitative interviews with village leaders, local government officials, and residents. The findings reveal that although the program has raised awareness and involved community participation, certain challenges such as lack of resources, insufficient coordination between agencies, and inadequate monitoring persist. These factors have impacted the overall efficiency and sustainability of the program. Furthermore, the study highlights the need for enhanced collaboration between local authorities and national drug enforcement bodies, as well as increased funding and training for community leaders. In conclusion, while Desa Bersinar has made significant strides in addressing drug issues in Semarang, more focused efforts are needed to improve its long-term effectiveness. Recommendations include reinforcing local support structures and creating better strategies for continuous monitoring and evaluation. This research contributes to the understanding of community-driven approaches in the fight against drug abuse at the village level.